Analisis Pemilihan Sepeda Motor Listrik Berbasis BOK di Kota Palangka Raya - Kemuning Gulo; Sutan Parasian Silitonga; Desriantomy (Jurnal Serambi Engineering, 2024)
The population growth in the city of Palangka Raya is increasing every year, therefore the use of transportation is also increasing. One environmentally friendly transportation product is an electric motorbike. This research specifically aims to analyze the selection of BOK-based electric motorbikes in the city of Palangka Raya. Data collection was carried out through face-to-face interviews with electric motorbike users and distributing questionnaires online using Google Form. The data obtained was processed using the PCI method and Microsoft Excel using descriptive analysis techniques and Binary Logit Regression. Based on the results of calculating vehicle operational costs using the PCI method, the results per kilometer are as follows: Conventional Scoopy motorbikes are Rp. 1,251, Beat Btreet type Rp. 1,485, Mio Fino type Rp. 1,562, and the Vespa type is Rp. 1,994. Viar N1 type electric motorbike for IDR. 1,096, U-winfly N9 type Rp. 683, U-winfly T3 type Rp. 572 and the Pacific type is Rp. 657. Selection of vehicles based on vehicle operational cost calculations shows that electric motorbikes are more economical to use than conventional motorbikes